A tese de performatividade e o ambiente das ideias: O papel dos modelos formais em economia - Neris, Celso; Fucidji, Josï¿½ Ricardo [UNESP] (FapUNIFESP (SciELO), 2014)
This paper examines the ‘performativity of economics’ thesis and uses it as an argument for the influence economic models may have on the economy. Although the performativity thesis has been the target of important critiques – even being called ‘vogue’ or ‘trendy’ theory sometimes – its weaker version simply claims that theoretical entities can have effects on economic agents’ practices. If this weaker version is admitted, it is worthwhile to discuss the reasons why economists adopt formal models, even though they are obviously unrealistic. We find one of these reasons in the institutions of economics and its processes of epistemic legitimization. By assuming that such a choice may lock economists in a ‘bad equilibrium’ regarding their aim of understanding and acting in the economy, this paper argues for greater ontological awareness about model building and use.
The performativity thesis and the environment of ideas: The role of formal models in economics
Keywords: Formal models; Ontology; Performativity thesis